2014
DOI: 10.1177/2150135114543388
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Unroofed Coronary Sinus With Cyanosis After Ventricular Septal Defect Closure

Abstract: Cyanosis after surgical closure of ventricular and/or atrial septal defect is very unusual. We report a case of unroofed coronary sinus in a six-month-old boy who developed cyanosis after surgical closure of ventricular and atrial septal defects. Clinical presentation, diagnosis, and management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Another 4 surgical patients who had been preoperatively diagnosed with URCS by CTA, no information was available regarding the management of URCS in their previous operative reports. It's worth noting that URCS may be missed by imaging or even during surgical repair due to its hidden location (26)(27)(28). The chances of leaving URCS untreated during surgical operation was possibly even higher, which occurred in 7 out of 30 patients in this series.…”
Section: Hemodynamics Of Urcs Detected By Ctamentioning
confidence: 81%
“…Another 4 surgical patients who had been preoperatively diagnosed with URCS by CTA, no information was available regarding the management of URCS in their previous operative reports. It's worth noting that URCS may be missed by imaging or even during surgical repair due to its hidden location (26)(27)(28). The chances of leaving URCS untreated during surgical operation was possibly even higher, which occurred in 7 out of 30 patients in this series.…”
Section: Hemodynamics Of Urcs Detected By Ctamentioning
confidence: 81%
“…7 Yarrabolu et al reported that they found UCS in a 6-month-old boy who developed cyanosis after surgical closure of VSDs. 8 Mallula et al reported that they successfully completed the PLSVC and coronary sinus ASD in a 2-month-old case with TOF. 3 Ramman et al found UCS in a patient with operated TOF and PLSVC who developed post-operative hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary resistance was also increased to 3.8 Woods units. The pulmonary pressure gradually decreased and the URCS was monitored clinically [3]. The pulmonary hypertension was initially managed with inhaled nitric oxide and supplemental oxygen and later with oral Sildenafil for 3 months.…”
Section: Casementioning
confidence: 99%